A new Leipothrix (Trombidiformes: Eriophyoidea) infesting Actinidia fruit trees in Jilin province, Northeastern China. Issue 7 (2nd October 2020) - Han, Xiao; Wang, Yue; Liu, Kai-Cheng; Ai, Jun; Chen, Ri-Zhao
ABSTRACT: A new mite species belonging to Eriophyidae (Trombidiformes: Eriophyoidea) from Jilin Province, northeastern China, is described and illustrated. Leipothrix argutae sp. nov . causes rust on its host plant, Actinidia arguta (Siebold & Zucc.) Planch. ex Miq. (Actinidiaceae), commonly known as hardy kiwi fruit. Protogyne and deutogyne morphs were found and described.